Effect of Overweight and Obesity on Periodontal Treatment Intensity. (April 2023) - Kaye, E.; McDonough, R.; Singhal, A.; Garcia, R.I.; Jurasic, M.
Introduction: Obesity is associated with greater utilization of medical resources, but it is unclear if a similar relationship exists for dental care. Objectives: This retrospective cohort study compared periodontal disease treatment among obese, overweight, and normal-weight patients attending an urban US dental school clinic. Methods: Periodontal, demographic, and medical history data for 3, 443 adult patients examined between July 1, 2010, and July 31, 2019, were extracted from electronic health records. Body mass index (BMI) was computed from self-reported height and weight and categorized as obese (≥30 kg/m 2 ), overweight (25–29.9 kg/m 2 ), or normal (18–24.9 kg/m 2 ). Periodontal disease was categorized using clinical probing measures. Procedure codes defined treatment type (surgical, nonsurgical, local chemotherapeutics, or none). Logistic regression models controlling for initial periodontal disease severity, age, gender, tobacco use, history of diabetes, dental insurance type, and follow-up (log of days) estimated odds ratios (ORs) and 95% confidence intervals (CIs) of any treatment among obese and overweight relative to normal-weight patients. The association between BMI and a periodontal treatment intensity score, based on treatment type, number of teeth treated, and number of visits, was evaluated with multivariable negative binomial regression. Results: Mean age at baseline was 44 ± 15 y, and severe periodontal disease was present in 32% of obese, 31% of overweight, and 21% of normal-weight patients. Average follow-up was 3.9 ± 1.6 y. Obese and overweight patients were more likely to have nonsurgical scaling and root planing or surgical procedures than normal-weight patients. Adjusted odds of any treatment were higher among obese (OR = 1.34; 95% CI, 1.14–1.72) and overweight (OR = 1.18; 95% CI, 0.97–1.42) relative to normal weight. Obese and overweight patients had 40% and 24% higher treatment intensity scores, respectively, than normal-weight patients. Conclusion: These results indicate obese and overweight individuals require more intensive periodontal treatment compared to normal-weight individuals, independent of initial disease severity. Knowledge of Transfer Statement: The results of this study can be used by dental providers and policymakers to better understand patient characteristics that influence the variability in frequency and length of periodontal treatment. Knowledge of a patient's body mass index may be useful in identifying patients who possibly will have a poorer periodontal prognosis.